Integration of Renewable Energy in Water Management Systems in Remote Areas: A Systematic Review - Darwis Baso (Universitas Islam Raden Rahmat, Malang, 2026)
Limited access to energy and clean water services remains a major barrier to socio-economic development in remote areas, particularly in off-grid regions with very limited electricity infrastructure. This study presents a systematic review of renewable energy integration in water management systems, focusing on energy-water access challenges, technology characteristics, and conceptual suitability. A literature selection followed the PRISMA protocol for national and international journal articles published between 2021 and 2025. A total of 36 articles met the inclusion criteria, covering renewable energy technologies such as solar water pumping, micro-hydropower, small-scale wind systems, rainwater harvesting, and hybrid configurations. The findings indicate that decentralized water systems based on renewable energy especially solar pumping and micro-hydropower demonstrate the highest suitability due to good energy efficiency, low operation and maintenance costs, and minimal infrastructure requirements. Hybrid systems further enhance service reliability through energy source diversification and storage, although they involve greater system complexity. Implementation success is influenced not only by technical performance but also by institutional capacity, community skills, and social readiness. Overall, integrating renewable energy strengthens the energy-water nexus, expands access to basic services, and supports sustainable development in remote areas, with recommendations for field testing and further optimization of hybrid systems.